The Post-war Japan: from historiography and literature. The case of Hilda Chen-Apuy and Yukio Mishima (1952-1982) - Vargas Alvarado, Víctor Julio (2022)
This article pretends to analyze the development of postwar Japan, what is known as its "second modernization", using both historiographical sources and literary essays as a historical source since literary works are a reflection of the society in a certain historical moment. In this manner, they can both produce and reproduce existing inequalities of power, or in contrast, propose another possible reality opposed to the current world. Furthermore, essays written by the Japanese author Yukio Mishima (1925-1970) and by the Costa Rican Hilda Chen-Apuy (1923-2017) are used, evidencing that they were questioners of the social, historical, and cultural reality of the modernization of post-war Japan, but from unequal perspectives and with different interests, which is directly related to their lives, ideals, beliefs, and values.